The Effect of Learning Style on the Pretest Results of Animal Histology and Embryology Practicum for Biology Education Students UAD Batch 2023 - Pujiastuti , Septi; Andriyani , Acie Putri; Fatmawati , Leli (Universitas Ahmad Dahlan, 2023)
Understanding of lecture material requires not only theory, but also in-depth practicum. In an effort to improve learning outcomes, it is important to understand the various factors that can affect student learning outcomes, one of which is learning style. Learning style is a way or method used by individuals to receive, process, and remember information. This study aims to examine the effect of learning style on the results of the pretest of animal histology and embryology practicum in Biology Education students at Ahmad Dahlan University, class of 2023. This study is included in quantitative research, which identifies the effect of variable X on variable Y. The research instruments used include a learning style questionnaire with a total of 10 questions. The data obtained were analyzed using descriptive statistical analysis in the form of a normality test and a T test. The results of the normality test showed that the significance value obtained was more than 0.05, which means that the data was normally distributed. The results of the T test showed a significance value of 0.00 less than 0.05. This shows that there is a significant influence between learning style and student pretest results. Based on the results, it can be concluded that there is a significant influence between learning style and student pretest results in the Animal Histology and Embryology practicum.